Adalimumab for refractory pulmonary sarcoidosis. (November 2016) - Minnis, P.; Poland, M.; Keane, M.; Donnelly, S.
Abstract Background Ireland has one of the highest prevalence of sarcoidosis globally. Currently anti-TNF treatment in sarcoidosis is considered on a case-by-case basis particularly in patients who have a sub-optimal response to corticosteroid therapy. Aims We report our experience of Adalimumab in a series of refractory pulmonary sarcoidosis and discuss implications for treatment. Conclusion Symptomatic improvement was found in all patients as well as stabilisation or improvement in DLCO sb. Improvements in pulmonary function tests correlated well to radiological stage and length of disease.